DESIGN OF HYDROXY XANTHONES DERIVATIVES AS ANTICANCER USING QUANTITATIVE STRUCTURE-ACTIVITY RELATIONSHIP - Yuanita, Emmy; Pranowo, Harno Dwi; Jumina, Jumina; Mustofa, Mustofa (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the research is to design a new hydroxy xanthone derivative has anticancer activity using quantitative structure-activity relationship (QSAR). Methods: The QSAR designed new compounds were calculated by parameterized model 3 methods and analysis of multi-linear regression (MLR). Result: The result showed that the best model as follows: LogIC = –9.132 qC1 + 28.853 qC5 + 2.456 qC6 – 7.375 qC10 – 5.112 qC11 + 3.900 This result has appropriate some statistical parameters (n=24; PRESS=0.999; r 50 2 =0.782; SEE=0. 235; R=0. 885; F cal /F Conclusion: This Model could be used to design of halogen-substituted hydroxy xanthone scaffold and predict their inhibitory concentration (IC tab =4.68). ) as anticancer in the range of 0.001 - 0.484 μM. Keywords: Anticancer, Quantitative structure-activity relationship, Xanthone. 50